Identifikasi Taenia solium secara Mikroskopis pada Peternakan Babi - Bekti, Heri Setiyo; Habibah, Nur; Rinawati, Luh Putu; Pradnya Yasa, Ni Putu Candra Dewi; Rindi, Oktavelendi Dhaneta Graha; Dewi, Ni Km Ayu Kusuma; Savitri, Ni Putu Ayu Dani; Rakhmawati, Aprilia (Politeknik Kesehatan Tanjung Karang, 2021)
Taenia solium is a zoonosis found all over the world, especially in developing countries. T solium can cause taeniasis and cysticercosis in humans. Pigs as intermediate hosts can be infected with T solium which causes porcine cysticercosis. T solium can infect muscle, skin, eye, and brain tissue which can develop into neurocysticercosis. Neurocysticercosis is the cause of 30% of cases of epilepsy in the world. In Denpasar city, pigs are one type of livestock. A large number of pig farms and the Balinese’s people's habit of consuming pork is one of the sources of T solium infection. This research was conducted to determine T solium eggs in pig feces. The study was conducted microscopically on 31 samples with simple random sampling technique. The results showed that of the 31 samples examined, 54.8% (17 samples) were positive for T solium eggs. This indicates that the pig farms in Denpasar city have been infected with T solium. Pig farming in Denpasar city was done traditionally and kept indoors. However, the breeders pay less attention to pig health and environmental sanitation. Also, pigs are slaughtered privately by breeders because there are no slaughterhouses. Lack of supervision of pork circulating in the community is also the cause of T solium infection. Therefore, it is necessary to carry out supervision by the local government on pig farms as well as supervision of pork consumed by the public to prevent and eradicate T solium infection.